Fabrication‐controlled morphology of poly(butylene succinate) nano‐microcellular foams by supercritical CO2. (2nd May 2018) - Zhang, Shuidong; Xu, Yue; Wang, Peng; Peng, Xiangfang; Zeng, Jianbing
Abstract : Poly(butylene succinate) urethane ionomer (PBSUIs) foams with nano‐microcellular morphology were fabricated using supercritical CO2 (sc‐CO2 ) at different parameters. Effect of urethane ionic group (UIG) content (ranged from 1% to 5%) on the rheology and crystallization of PBSUIs were evaluated by intrinsic, dynamic rheological, X‐ray diffraction, and differential scanning calorimetry measurements. The results show that the complex viscosity of PBSUIs vastly improved, while their intrinsic viscosity and crystallinity decreased. They also evidenced that CO2 promoted the formation of crystallites in the amorphous and increased the Xc of PBSU and PBSUIs foams. Scanning electron microscope was employed to explore the influences of UIG content and foaming parameters on the morphologies of PBSUIs microcellular foams, and it revealed that UIG content was the dominated factor. The cell size and cell densities of PBSUIs microcellular foams were smaller than 5.0 micrometers and higher than 1.5 × 10 10  cells/cm 3, respectively, even foamed at diverse variations of foam temperature and pressure. Interestingly, PBSUIs with 3% and 5% UIG content achieved microcellular foams in nano‐cells, high‐stretched elliptical shape. The mechanism was ascribed that these PBSUIs with high melt viscosities could retard the CO2 bubbles to merge during the foam process and induce the cells to stretch and orient in depressururization direction. This study proposed a novel method for fabricating PBS nano‐microcellular foams.